The relationship between work stress factors and job satisfaction among quantity surveyors at consultant firms in Kuching, Sarawak - Teng, Michael Loong Ing (Universiti Malaysia Sarawak (UNIMAS), 2011)
In this modern era, the construction development has increased the demand for the construction consultant especially the Quantity Surveyor. Construction field requires frequent communication among the parties involved in a particular project. Employers expect that QS from any universities are able to strive and perfonn well for the organization. Those who are capable in immersing themselves in QS profession will have the better chances for employment and vice versa. This capability refers to the ability to manage well the work stress and eventually achieve the job satisfactio~ Hence, this research is mainly to identify the relationship between work stress factors and job satisfaction among QS at consultant finns in Kuching, Sarawak. 57 QS from 15 active consultant finns available in Kuching were the respondents for this research. Questionnaire was the main instrument used to get the primary data. The data were further analyzed by using SPSS 16.0 Version Statistical Package for Social Science (SPSS) to seek for the relationship between the variables. From the research, it can be concluded that gender has no implication on the QS job satisfaction. Male or female QS in Kuching are satisfied with the current career specifically at consultant finns. In addition, this research found that group inter-relationship is the dominant factor that influence QS job satisfaction. The finding could helps consultant finns to take the initiative to enhance relationship among employees as to boost their work perfonnance.